Crowdfunding e os critérios materiais de impostos incidentes (IR, ITCMD, ICMS E ISS): análise à luz do constructivismo lógico-semântico - Sukar, Rayane Gomes Dornelas Alcoforado (2022)
This dissertation seeks to examine the material criteria of the Income Tax, the Donation Tax, the Tax on Circulation of Goods and Services, and the Tax on Services Rendered of Any Nature, incident on crowdfunding operations in the donation, reward, pre-sale, and loan systems. In this context, the issues pertaining to semiotics, the theory of legal rules, the operation and legal nature of crowdfunding in Brazil will be examined in detail, as well as the analysis of the material criteria of the taxes in question as opposed to each mode of collective financing subject of this research. To develop the theme, the tool of Logical-Semantic Constructivism is used, in order to investigate the theory of the legal norm and the phenomenology of tax incidence in the light of the effectiveness of the law. The use of this method will be essential to the analytical isolation of the material criteria of the legal norm of each tax studied and then compare it with each of the modalities of collective financing, always observing the tripartite relationship of crowdfunding (project author—platform— supporter). The starting point of this research was the qualitative bibliographical review specialized in tax law, based on the collection available at the journals' portal of Coordination of Improvement of Personal Higher Education (Capes) and at the Brazilian Digital Library of Theses and Dissertations (BDTD), produced by legal scientists and reviewed by their peers. Finally, it is understood that the Brazilian positive system provides, through its legal rules, sufficient elements for the fair characterization of the incidence of the taxes mentioned on the operations of collective financing, which, as a method of fundraising, has been presented as a growing practice